Learning strategies in distance nursing education during the COVID-19 lockdown: a cross-sectional analysis - Ait Moussa, Khadija; Selmaoui, Sabah; Ouzennou, Nadia (Institute of Advanced Engineering and Science, 2025)
The COVID-19 pandemic led to a rapid transition to distance learning (DL), significantly affecting nursing students due to the disruption of essential practical training. This cross-sectional descriptive study examines the learning strategies (LS) adopted by 200 students at the Higher Institute of Nursing and Health Techniques of Marrakech (ISPITS-M) and identifies the factors influencing their adoption. Data were collected using a structured, expert-validated questionnaire (Cronbach’s alpha=0.72). Statistical analyses, conducted using SPSS (version 25.0), included descriptive, bivariate, and multivariate analyses. The findings indicate a predominance of metacognitive strategies, such as planning and time management (63.8%), and cognitive strategies, including memorization (58.9%), which were often adopted intuitively. The blended learning mode (synchronous and asynchronous) (OR=0.621; p=0.013) and student satisfaction with pedagogical modalities (OR=1.446; p=0.019) emerged as key determinants of learning strategy adoption. These findings underscore the need to develop structured blended learning environments that foster interaction, student engagement, and digital competency training. Implementing targeted pedagogical interventions could enhance academic performance and adaptability, addressing the specific needs of health sciences education while promoting long-term student success.